2014
DOI: 10.1155/2014/963791
|View full text |Cite
|
Sign up to set email alerts
|

Review of Input Congestion Estimating Methods in DEA

Abstract: Congestion is an economic phenomenon in the production process where excessive amounts of the input cause a reduction of the output. The motivation of this paper is to investigate and compare the methods provided for estimating congestion in the DEA literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In this case, according to the constraints of Model ( 9) in the optimal solution, relation (17) holds: ¼ l j ðk ¼ 1; :::; q; j ¼ 1; :::; nÞ, Model (9) is clearly transformed to Model (2). This shows that any feasible solution of Model (2) is also a feasible solution of Model (9).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In this case, according to the constraints of Model ( 9) in the optimal solution, relation (17) holds: ¼ l j ðk ¼ 1; :::; q; j ¼ 1; :::; nÞ, Model (9) is clearly transformed to Model (2). This shows that any feasible solution of Model (2) is also a feasible solution of Model (9).…”
Section: Plos Onementioning
confidence: 99%
“…Wie and Yan [ 16 ] studied the problems of congestion using the DEA output-oriented models. Further studies in this field can be found in the work of Khodabakhshi et al [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the research program input scale, such as team size and grant size, does not change proportionally, the output of NSFC will not always increase with an increase in grant size input, and sometimes even output will be congested. Congestion is a special return to scale (Wei and Yan, 2004) [58] and in this paper it means that excessive amounts of an input lead to a reduction in the output (Khodabakhshi, et al (2014) [59]). Thus, on the basis of the directional RTS introduced by Yang et al [53] and the congestion research of Wei and Yan et al [58], we investigate the directional RTS under congestion.…”
Section: Directional Dea Model and The Determination Of Rts Under Con...mentioning
confidence: 99%
“…Hosseinzadeh Lotfi et al [16] used the one-model approach to estimate the input congestion in five Iranian banks, with two stochastic inputs and two outputs. A review of the different approaches to identifying the input congestion of DMUs in DEA can be found in Khodabakhshi, Hosseinzadeh Lotfia, and Aryavash [24]. The aim of the present paper is to determine the input congestion of DMUs using a BCC input relaxation model with precise and imprecise data.…”
Section: Introductionmentioning
confidence: 99%